Is climate neutral possible for the U.S. beef and dairy sectors? - Thompson, L. R.; Beck, M. R.; Larson, H.; Rowntree, J. E.; Place, S. E.; Stackhouse-Lawson, K. R. (Frontiers in Sustainable Food Systems, 2025)
The objective of this review and modeling effort is to define climate neutrality as it relates to beef and dairy production, and to introduce accounting methods that will help guide the livestock industry’s ability to achieve climate targets, to summarize emission mitigation strategies, and present potential scenarios to achieve climate neutral emissions for the beef and dairy industries. The global target to limit global warming to 1.5°C above pre-industrial levels by 2050 has resulted in many companies, including agribusiness companies, setting voluntary emission reduction targets. The main concept behind these goals is that GHG emissions do not exceed the GHG removed from the atmosphere by GHG sinks. Where multiple greenhouse gases are involved, the quantification of climate neutral emissions depends on the climate metric and time horizon chosen to place these gases on an equivalent basis (e.g., global warming potential, and global warming potential-star). As the ruminant supply chain emits both short-lived (methane; CH4) and long-lived (carbon dioxide and nitrous oxide) GHGs, how companies choose to account for these gases will impact their progress toward these goals. Further, mitigation strategies for beef and dairy systems have predominantly focused on enteric CH4 emissions and soil C sequestration. However, several hurdles still exist to reduce emissions by the magnitude required to realistically achieve a net zero supply chain. Determining the ability of a system to be climate neutral is a complicated and complex process and will not be achieved by a “silver bullet” approach. The scientific community will need to develop multiple mitigation strategies that are regionally and contextually adaptable.